AB1085 OSTEO-ARTICULAR MANIFESTATIONS OF SARCOIDOSIS: ABOUT 13 CASES. (June 2019) - Mohamed Amine EL, ACHEK; Baccouche, Khadija; Farhat, Amel; Amri, Nejla El; Zeglaoui, Hela; Bouajina, Elyes
Abstract : Background: Sarcoidosis is a systemic disorder of unknown etiology, affecting the respiratory tract and the lymphatic system with predilection. It is an ubiquitous condition whose clinical phenotype is very diverse. Objectives: To detail the epidemiological, clinico-biological, therapeutic and evolutionary features of osteoarticular forms of sarcoidosis. Methods: This is a monocentric, descriptive retrospective study conducted over a 17-years period [2002-2018] involving 13 patients diagnosed with sarcoidosis with osteoarticular manifestations at the department of Rheumatology at Farhat Hached University Hospital in Sousse. Results: 13 patients with osteoarticular manifestations were studied; this was indicative of the disease in 8 cases (61.5%). The sex ratio was 0.23 with a mean age of 42.38 years and a diagnostic delay of 12 months. In 77% of cases, inflammatory arthralgia was noted, Löfgren syndrome (30.7%), chronic polyarthritis (30.7%), phalanges cystoid osteitis (15.4%) and no cases of monoarthritis. The extra articular manifestations found were; Adenomegaly (92.3%), lung (77%), cutaneous (38.5%) (including 80% erythema nodosum), neurological (30.7%) (Aseptic meningitis and convulsion), ocular (23%) (chorioretinitis, keratoconjunctivitis and retro-bulbar optic neuritis), cardiac (15.4%), and biological hepatitis (7.7%). In the biology, a biological inflammatory syndrome was found in 30.7% with a mean sedimentation rate of 31.07 in the 1st hour, an average CRP of 9 mg/L, cholestasis and cytolysis found in 15.4% and 7.7%, respectively. No Hypercalcemia was noted. The value of the conversion enzyme was high in 5 out of 6 patients who were dosed with an average of 71 μg/L. In imaging, sarcoidosis was destructive in 4 cases; A multifocal osteonecrosis, Algodystrophy of the two hips and two cases of bullous cystoid osteitis of phalanges. Conclusion: The osteo-articular involvement of sarcoidosis is polymorphic, which can reveal the disease or enamel its evolution. Disclosure of Interests: None declared